Hamdi Dahir. Cooperazione sociale ed economica in Africa orientale - Carlucci, Francesco (Rivista di studi politici internazionali, 2009)
ABSTRACT - Several Countries forming that part of the world we call Eastern Africa: Somalia, Kenya, Sudan, Ethiopia, Eritrea, are often taken into consideration by mass-media because of bloody and devastating wars, but these subjects are dealt with at length by magazines, books and other means of communication. Public opinion is appropriately informed. On the contrary, we believe that the following topic, directly originating from this situation, is quite interesting: the attempt of overcoming this state by means of the social and economic co-operation, realized through the institution of a supranational intergovernmental authority, the Igad (Intergovernmental Authority on Development), with the charge of fostering the human development of seven Countries in Eastern Africa, Ethiopia, Sudan, Kenya, Uganda, Somalia, Eritrea and Djibuti (a group of Countries called «Greater Horn of Africa») in a co-ordinated way. The paper illustrates this topic. Its first part shows the current conditions of the seven countries. The existing war situation is summarized, which is originated by the past European colonization, the current geopolitical aims of at least three great powers (the United States of America, Russia and China) and some specific characters of the States in that Region after their independence. Afterwards, the problems caused by the utilization of the Nile waters are exposed and three sections define the main aspect of human development in the seven Countries: one on demography, health and nutrition; one further on education, environment and infrastructures; a third on economy. The second part of the paper analyzes the structure of economic, social and political co-operation in the Region; Igad’s objectives together with the first results as well as the efforts made to solve the conflicts by means of an early warning system, addressed to prevent them, are described. Afterwards, the main problems that the co-operation initiatives should solve are shown, stressing the importance of Nile waters as the chief water resource, and of the infrastructural, trade, health, energy, agricultural and zootechnical policies. The process of co-operation in Eastern Africa is difficult and long, but onlythat can give the hope of solving the problems that face the ountries in the Region. RÉSUMÉ - Pays divers constituants la partie du monde que nous appelons Afrique orientale, la Somalie, le Kenya, le Soudan, l’Ethiopia, l’Eritrea, actuellement sont l’objet de l’attention des moyens de communication de masse à cause des guerres sanglantes qui les ont dévastés. Journaux, livres et moyens d’information développent largement les thèmes relatifs: l’opinion publique est donc convenablement informée. Nous pensons, par contre, qu’un sujet à la suite de cette situation soit d’intérêt primaire: la tentative de dépasser cette situation au moyen de la coopération sociale et économique, réalisée par l’institution d’une autorité entregouvernementale supranationale, l’Igad (Intergovernmental Authority on Development), ayant la fonction d’encourager en forme coordonnée le développement humain de sept pays de l’Afrique orientale: l’Ethiopia, le Soudan, le Kenya, l’Ouganda, la Somalie, l’Eritrea e le Djibouti (la Corne de l’Afrique étendue). Le présent essai illustre ce point. La première partie nous montre les conditions actuelles des sept pays de la zone. On y a résumé la situation de guerre qui y existe, dérivée soit de la colonisation européenne passée soit des visées géopolitiques actuelles d’au moins trois grandes puissances (les États-Unis d’Amérique, la Russie et la Chine) soit de quelques caractères des États régionaux après leur indépendance. A suivre, l’exposition des problèmes qui dérivent de l’utilisation de l’eau du Nile et ensuite trois paragraphes qui font le point sur les aspects principaux du développement humain dans sept pays: le premier sur la démographie, la santé et la nutrition; le deuxième sur l’instruction, l’environnement et les infrastructures; et le troisième sur l’économie. Dans la deuxième partie de l’essai on analyse la structure de la coopération économique, sociale et politique entre les États de la région, on décrit les objectifs de l’Igad avec les premiers résultats obtenus, ainsi que les efforts faits pour la solution des conflits dans la zone avec le développement d’un système d’alarme ayant la fonction de les prévenir. On a après montré les problèmes principaux que les initiatives de coopération devraient résoudre, en mettant un accent particulier sur l’usage de l’eau du Nile comme ressource hydrique principale, les infrastructures, les politiques commerciales, les agricoles, les zootechniques, les sanitaires et les énergétiques. Le processus de coopération en Afrique orientale sera difficile et long, mais uniquement dans ce processus on peut trouver l’espoir d’une solution possible des nombreux problèmes qui tenaillent les Pays de la région.